Knowledge of the Weapon in Party Liability Cases: An Analysis of Edmonds v R - Hill, Amy (Victoria University of Wellington Law Review, 2013)
This article explores the reasoning in Edmonds v R, the leading case in New Zealand on knowledge of the weapon in party liability cases. The Supreme Court concluded that there is no legal requirement to direct that a defendant must have known of a weapon to be guilty as a secondary party. There is a dichotomy between the approach in New Zealand and that adopted in the United Kingdom in similar situations. New Zealand has adopted an approach focused on harmful outcome whereas the United Kingdom decisions suggest a focus on the process involved in the crime. Because of these differing attitudes, it is undesirable for New Zealand to follow the United Kingdom in adopting a “knowledge of the weapon” direction as a matter of course in party liability trials. However, it appears that many lower court judges feel it is appropriately conservative to consider the defendant's foresight of a weapon for practical, evidential reasons. That approach has several merits but must remain confined to evidential aspects of the trial.